Efeitos do treinamento da musculatura inspiratória em atletas de judô - Bueno, J. H.; Kutchak, F. M.; Rossato, D.; Peixoto, J. L. L.; Müller, A. B. (Revista Brasileira de Prescrição e Fisiologia do Exercício, 2023)
Judo is a sport with intermittent characteristics, where the athlete makes great efforts in a short period of time. For this reason, the muscle fibers used during sports practice re type two fibers, which use glucose as an energy source, its turn ends up resulting in an accumulation of lactate in the athletes' bloodstream, causing the inspiratory metaborreflexo to be activated and the athlete to enter into peripheral muscle fatigue. The aim of this study is to analyze the effects of inspiratory muscle training on Judo athletes. Respiratory muscle strength was assessed through maximum inspiratory pressure, maximum expiratory pressure, and athletes' functional capacity through the Special Judo Fitness Test. Nine athletes` participated in this study, with an average of 21,6 years. It was observed that in the pre-training moment, the athletes presented a decrease in respiratory muscle strength and a classification index of 13,00. After training, there was a significant improvement in respiratory muscle strength and a better classification index of the functional capacity test, to 11,9. In this way, inspiratory muscle training is beneficial for Judo athletes, improving their respiratory strength and physical capacity.